Development of agricultural mechanization in Ghana: Network, actors, and institutions: A case study of Ejura-Sekyedumase district - Cossar, Frances; Houssou, Nazaire; Asante-Addo, Collins (International Food Policy Research Institute, 2016)
This paper characterizes the network of tractor service providers in Ghana. Using the case of Ejura-Sekye-dumase district, this research examines the implications of the adoption of mechanical technology in agriculture for farmers and institutions based on perspectives that go beyond the suppliers and users of mechanization ser-vices alone. The results suggest that, in addition to rising population density and favorable access to local and regional markets, the current pattern of use of tractors by farmers in Ejura district emerged from favorable histori-cal and institutional factors. The current arrangement involving a network of private tractor owners providing trac-tor hire services to a broad set of farmers draws upon the legacy of an earlier institutional intervention and is sus-tained organizationally through kinship and other existing social relationships within and outside the district. More-over, the expansion of tractor use has created a set of new roles and relationships within the network. Participa-tion in the network is affected by various factors, including farmer’s access to capital and knowledge, experience, and contacts. This privately operated network is significantly more efficient and provides small-scale farmers with considerably better access to plowing service than did previous government-managed systems. Further develop-ment of the tractor service sector is likely to improve the quality of mechanization offered to smallholder farmers, enhance bargaining power for farmers seeking such services, and reduce structural weaknesses within the net-work.